Clinico-Biochemical Effects Of Different Anthelmintic Combination Against Common Fluke Infestation In Buffaloes - Sinha, Ranveer Kumar; Kumari, Bibha; Kumar , Bipin (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was undertaken on clinico-biochemical status in healthy and naturally infected buffaloes with fasciolosis and its therapeutic management through different anthelmintic combination. TSP, albumin, globulin and A/G ratio were found to be reduced as compared to healthy, whereas SGOT and SGPT were found to be significantly higher in infected buffaloes. Recovery was observed in different clinico-biochemical parameters on treatment with combination of oxyclozanide and albendazole @ 15 mg/kg.b.wt., followed by oxyclozanide + tetramisole and oxyclozanide alone. It is also revealed that apart from chemotherapy, supportive therapy helped in speedy recovery of different biochemical parameters and in gaining normal health after elimination of parasite.
Keywords: Anthelmintic; Flukicidal; Metabolic Activity; Oxyclozanide